2015
DOI: 10.1016/j.jnucmat.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Palladium interaction with silicon carbide

Abstract: a b s t r a c tIn this work the palladium interaction with silicon carbide is investigated by means of complementary analytical techniques such as thermogravimetry (TG), differential scanning calorimetry (DSC), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS).Thermoscans were carried out on pellets of palladium, a-SiC and b-SiC high purity powders in the temperature range comprised between 293 K and 1773 K, in order to study the effect of temperature on the palladium-silicon carbide reaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Furthermore, SiC begins to gradually lose mechanical integrity especially above 1700 C, by transformation of -SiC to -SiC and later thermal decomposition [26][27][28]. It is also widely noted that the SiC layer is subject to attack from palladium and rare earth elements [21,[29][30][31][32][33][34], although some studies led to contradictory results, showing significant Pd corrosion of SiC has not been identified [16,35].…”
Section: Triso-coated Particle Fuelmentioning
confidence: 99%
“…Furthermore, SiC begins to gradually lose mechanical integrity especially above 1700 C, by transformation of -SiC to -SiC and later thermal decomposition [26][27][28]. It is also widely noted that the SiC layer is subject to attack from palladium and rare earth elements [21,[29][30][31][32][33][34], although some studies led to contradictory results, showing significant Pd corrosion of SiC has not been identified [16,35].…”
Section: Triso-coated Particle Fuelmentioning
confidence: 99%
“…Ф Bo appears to be strongly influenced by the metal work function with a higher work function producing a higher Schottky barrier [12]. The highest increase for Pd devices is observed above 620 K. It has been reported that an exothermic reaction occurs between SiC and Pd in the 673 K-873 K range [31]. n generally decreases from 1.6 at 300 K to about 1.0 at 800 K for Ni, Co and Pd as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 87%
“…Other initiatives aimed at increasing tolerance to fault conditions, so-called 'accident tolerant fuels' (ATFs) are also being progressed, e.g. SiC-SiC composite cladding [13,14].…”
Section: Developments In Fuel Technologymentioning
confidence: 99%